Enhancing the mechanical strength and CO₂/CH₄ separation performance of polymeric membranes by incorporating amine-appended porous polymers - Yang, Yanqin (2021)
The incorporation of solid fillers into mixed matrix membranes (MMMs) is a promising approach to overcome the permeability-selectivity trade-off characteristic of polymeric membranes. However, MMMs that contain conventional fillers (e.g., zeolites, silicas, and porous carbons) usually exhibit defects due to incompatible interfaces between fillers and glassy polymers. High porosity and good robustness are also desirable properties of filler materials that enhance the gas separation performance of resulting MMMs. Herein, amine-functionalized organic porous polymers (PP-DETA and PP-menm) were synthesized and used as filler materials to yield mechanically stable MMMs that possess good CO2/CH4 separation performance. We found that in comparison with the MMMs loaded with bare porous polymers (PP), composite membranes that contain amine-functionalized fillers exhibited both superior mechanical strength and more effective adhesion to glassy Matrimid® Polyimide (PI) and polysulfone (PSf) polymers. In particular, the tensile strength of 10 wt%_PP-menm@PI was measured to be 69 MPa, which was higher than 26 MPa and 33 MPa for 10 wt%_PP@PI and pure PI membrane, respectively. More importantly, both the CO2 permeability and CO2/CH4 selectivity of MMMs improved significantly after the introduction of amine-functionalized fillers. These results imply that organic porous polymers, particularly those that contain amine-functional groups, are outstanding filler materials for the fabrication of defect-free MMMs with enhanced gas separation performance.